2001
DOI: 10.1002/1097-0142(20010801)92:3<578::aid-cncr1357>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality treatment of patients with liver metastases from germ cell tumors

Abstract: BACKGROUND The presence of liver metastases represents an independent poor risk prognostic factor for survival in patients with germ cell tumors. METHODS The clinical files of 37 patients who had undergone liver resection for the treatment of disseminated germ cell tumors were reviewed to define the indications for resection of residual liver metastases after chemotherapy in patients with germ cell tumors. The histologic patterns of primary tumor and residual disease were compared. The prognostic factors for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 36 publications
2
16
0
1
Order By: Relevance
“…Previous studies have found necrosis in 16-67%, teratoma in 12-51%, and viable cancer in 21-55%. 8,9,14 In our study, the distribution of these histologies was 33%, 13%, and 27%, respectively, with another 27% being benign hepatic lesions. While no study has specifically examined the role of preoperative hepatic biopsy and the concordance rate between hepatic histology found at preoperative biopsy versus at surgical resection, preoperative hepatic biopsy is only pursued if its findings would alter patient's overall treatment plan.…”
Section: Discussionsupporting
confidence: 45%
See 4 more Smart Citations
“…Previous studies have found necrosis in 16-67%, teratoma in 12-51%, and viable cancer in 21-55%. 8,9,14 In our study, the distribution of these histologies was 33%, 13%, and 27%, respectively, with another 27% being benign hepatic lesions. While no study has specifically examined the role of preoperative hepatic biopsy and the concordance rate between hepatic histology found at preoperative biopsy versus at surgical resection, preoperative hepatic biopsy is only pursued if its findings would alter patient's overall treatment plan.…”
Section: Discussionsupporting
confidence: 45%
“…6, 10-12 Experiences with resection of metastatic disease in the liver, however, have only been reported in four previous studies. 8,9,13,14 The current study demonstrated that (1) resection of hepatic metastases from GCT can be performed safely, (2) hepatic pathology may be discordant with extrahepatic disease and remain difficult to predict, and (3) long-term overall survival can be achieved. Thus, the experiences reported herein support the integration of hepatic metastasectomy into the multidisciplinary care of patients with metastatic GCT.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations